Ensuring effluent standards by improving the design of Rotating Biological Contactors - Mba, David; Bannister, R. H. (Elsevier Science B.V., Amsterdam., 2007)
The Rotating Biological Contactor (RBC) is used for both municipal and industrial wastewater treatment; however, the RBC has been plagued with mechanical deficiencies since its conception. The unpredicted loss of mechanical integrity results in loss of operation and the discharge, into the environment, of effluent that does not meet consent standards as set by governmental bodies. The consequence of the latter on aquatic life cannot be understated. Whilst maintaining an effluent standard is of vital importance this has to be balanced against the capital costs of RBC units. In addition to detailing reasons for defects associated with RBC’s this paper presents a novel design approach for shaftless RBC’s. This novel design takes cognisance of the mechanisms and reasons for mechanical failure, thereby reducing occurrence of loss operation of RBC units and ensuring that the effluent continually meets discharge standards. The added significance of the design is a 50% reduction in co
Keywords: Corrosion fatigue; Hydrogen embrittlement; Microbiologically influenced corrosion; Rotating biological contactor